Nursing Reduction Strategies to Enhance Estrus in Lactating Sows and Effects on Performance of Pigs to Market Weight - H. L. Frobose; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; R. D. Goodband; J. C. Woodworth; J. L. Nelssen; D. L. Davis (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 135 sows (PIC 1050), ranging from parity 1 to 5 (2.6 ± 1.4), were used in 5 consecutive farrowing groups (February to August). The objectives were to evaluate different suckling reduction strategies for inducing lactational estrus and the effects on sow fertility and piglet growth. Litter size was equalized within parity (11.5 ± 1.1 piglets) at d 2 after farrowing. At d 18, sows were assigned to 1 of 5 treatments (n = 26 to 28) based on parity, farrowing date, and suckled litter size. Treatments were: 1) control; 2) sows that were paired within parity and placed in adjacent stalls, on d 18 all but 5 of the lightest piglets were weaned, and the remaining piglets were combined and alternated between sows at 12 h intervals until d 25 (ALT); 3) piglets separated from sows for 12 h/d from d 18 to 25 (SEP); 4) all but the 5 lightest piglets weaned on d 18, split-weaning (SW); and 5) piglets separated from sows for 24 h on d 18 (24HR). Controls were weaned at d 21 with other treatments weaned at d 25. All sows were provided nose-to-nose contact with a mature boar for 5 min/d from d 18 until weaning without removing them from farrowing crates. Creep feed and water were provided from d 14 to weaning. Offspring ADG was recorded to market for 2 farrowing groups. Sow backfat and BW losses during lactation were similar across treatments. Of the 106 sows subjected to reduced suckling, 80 (76%) expressed estrus during lactation. The SEP and 24HR sows were in estrus earlier (P<0.05) than SW sows. A tendency for reduced conception rate was observed in SEP and 24HR sows (P<0.10) versus control and SW sows. Creep feed disappearance was greatest (P<0.01) for SEP and 24HR litters, and pig ADG from d 18 to 32 was reduced (P<0.05). No negative effects (P>0.05) on final BW or carcass composition were observed for the reduced suckling treatments. Altered suckling treatments differed in their ability to induce lactational estrus and their impact on gain immediately post-weaning. However, no benefits were observed for pig growth to market weight.
Keywords: boar exposure; intermittent suckling; lactational estrus; litter separation; split-weaning